THE INFLUENCE OF LIFESTYLE, REFERENCE GROUP, AND BRAND IMAGE TOWARDS BRAND LOYALTY ON NIKE SHOES - NUGRAHA, ABI MUHAMMAD (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2019)
This research aims to examine the influence of lifestyle, reference group, and brand image towards brand loyalty on Nike shoes product. This type of research is explanatory research. This research conducted on Nike shoes users. This questionnaire has been distributed 150 randomly to every consumer who has bought Nike shoes product. The sampling technique used purposive sampling and the research instruments were tested using the validity test, reliability test, and classical assumption test. The hypothesis used partial (t-Test). Results of the data analysis from multiple regression showed that lifestyle, reference group, and brand image have a significant effect partially to brand loyalty by consumers. From the test results, the dominant test show that variables reference group has a dominant to influence on brand loyalty. The results from this study can be applied to marketing strategy for companies and interested parties for enhancing and maximizing lifestyle, reference group, and brand image to get a positive effect that can lead to brand loyalty.Â Keywords: lifestyle, reference group, brand image, and brand loyalty.